Investigation of surface deposition in a simulated fuel injector feed arm with sudden expansion/contraction. (15th December 2016) - Alborzi, Ehsan; Blakey, Simon; Ghadbeigi, Hassan; Pinna, Christophe; Lewis, Christopher
Abstract: Formation of surface carbonaceous deposits at inner surface of two classes of simulated jet engine burner feed arm including a straight tube as well as two tubes with sudden expansion/contraction was studied using "Aviation Fuel Thermal Stability Test Unit (AFTSTU)". The generated results indicate that phenomena such as stagnant flow formation, flow separation and vena contracta have a substantial impact on surface deposition. Commercial "Computational Fluid Dynamics (CFD)" package, ANSYS Fluent was used to interpret the impact of flow features and heat transfer characteristics on surface deposition. The experimental data obtained in this work were used in a one dimensional heat transfer model for prediction of deposit thickness in simulated burner feed arms. Subsequently, the simulated burner feed arm with contraction/expansion structure were sectioned and prepared for deposit visualisation with "Scanning Electron Microscopy (SEM)". The results of visualised deposits are consistent with one dimensional heat transfer calculation. The novel set of experimental data presented in this work provides a basis for the construction of predictive models for calculation of deposit growth and total deposit mass in fuel injection system. A description of the model will be addressed in the second paper of this work which is currently under preparation.